CONTRASTIVE ANALYSIS OF HURUF 'ATHAF (ARABIC) AND CONJUNCTIONS (INDONESIAN): ANALISIS KONTRASTIF HURUF ‘ATHAF (BAHASA ARAB) DAN KONJUNGSI (BAHASA INDONESIA) - Bintang Rosada (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: Basically, every language has a grammar that includes phonetic, morphemic, syntactic, and cultural differences, so that differences in letter symbols are linguistic facts that cannot be ignored. just like when we want to understand Indonesian text with Arabic text, of course there are differences in interpreting and interpreting the two. languages ​​have special characteristics that can be identified through in-depth analysis. Arabic is the language with the largest number of words recognized by the world, has various meanings of each word. As for learning it is different from studying other languages ​​because Arabic has phonetics, morphemic, and syntax which we rarely encounter in other languages. The purpose of this study is to describe a contrastive analysis in giving meaning to letters / conjunctions, especially in studying the letters Athaf in Arabic and conjunctions in Indonesian. This research category is library research, with a linguistic approach, namely quoting, adapting, then analyzing. The method used is the method of contrastive analysis by comparing the meaning of the letter Athaf in Arabic and the conjunction in Indonesian, to see the differences and similarities between the two languages. This analysis is used to make it easier for students to understand the meaning of the letters Athaf and conjunctions in a sentence, so as not to cause doubts that lead to wrong understanding. Keywords: Contrastive Analysis, Athaf Letters, Conjunctions